“SHOULD I STAY OR SHOULD I GO?” UNDERSTANDING THE ANTECEDENTS TO BUYER COMMITMENT IN THE CONTEXT OF THE US EYECARE INDUSTRY - Poh-Lin Yeoh (Asian Academy of Management Journal, 2017)
This study extends the existing stream of research on channel relationship by examining the antecedents and consequences of firm commitment (i.e., affective and calculative) among small-sized firms in the United States (US) eyecare industry. Achieving strong growth in today’s primary eyecare market presents a challenge for many independents as they face new uncertainties from competition and regulatory reforms. Compounded by their inability to offer lower prices as well as lacking individual negotiating power with manufacturers, many small independent opticals have turned to buying groups to help reduce product acquisition costs as well as to stay competitive as independent entities. A mail survey of 200 independent opticals was conducted, and the data was analysed using structural equation modelling. The two dependent variables of interest are repurchase intentions and relational tolerance. The effect of affective commitment is positive and significant for both repurchase intentions and relational tolerance while calculative commitment only had a positive impact on relational tolerance. Findings further suggest that both transactionaland relational-specific investments help govern the relationship between buying groups and independents in an uncertain environment. Transaction specific investment increase independents’ calculative commitment as it creates value in the form of cost saving and profit enhancement. At the same time, this study corroborates arguments from social exchange theory regarding the role of relational mechanisms in reducing opportunism by enhancing independents’ affective commitment. However, while the bright side of social capital has often been the focus on buyer-seller relationships, the positive relationship between relational embeddedness and calculative commitment supports the emergent notion of the dark side of social capital.